Molecular and morphological identification of Phylloderma stenops Peters, 1865 (Chiroptera, Phyllostomidae) and new records for Colombia (2019)
ABSTRACT: Based on revisionary work of recently collected material in Colombian museums we confirm the presence of Phylloderma stenops Peters, 1865 in 6 new localities for the country, including the first record of the species in the dry lowlands of the northern Caribbean coast, and the increase by more than 800 m of the elevational range of the species in Colombia. DNA-barcoding confirmed our morphological identification, and supported a paraphyletic composition of the cis-Andean populations. Our records exemplify the little knowledge on the ecogeographic distribution of this species and provide further evidence to consider this as a widespread but rare species.